2019
DOI: 10.1021/acsami.9b11204
|View full text |Cite|
|
Sign up to set email alerts
|

Polysulfides Synthesized from Renewable Garlic Components and Repurposed Sulfur Form Environmentally Friendly Adhesives

Abstract: Natural materials have been used as glues throughout human history. Over the last century, society has come to rely heavily on synthetic, petroleum-based adhesives instead, consuming ∼14 million tons per year. In recent years, however, there has been a resurgence of glues formed with renewable materials. This work seeks to integrate the two to form strong adhesives. Here, elemental sulfur was combined with diallyl sulfide (DAS), diallyl disulfide (DADS), and garlic essential oil (GEO) to form adhesive polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 71 publications
1
77
0
1
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17] The ability to break the S-S bonds in these polymers has also been exploited in the insertion of monomers into the backbone of sulfur pre-polymers, [18][19][20] delayed curing systems, 20 and also in next-generation adhesives. 21 In these studies, S-S bond cleavage is provoked by heating-usually to temperatures near 100 C or higher. In one notable exception, Zhang has shown that sulfur polymer and liquid metal composites can self-heal at room temperature, but this adhesion is based on affinity of the sulfur for the metal rather than through S-S bond exchange.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17] The ability to break the S-S bonds in these polymers has also been exploited in the insertion of monomers into the backbone of sulfur pre-polymers, [18][19][20] delayed curing systems, 20 and also in next-generation adhesives. 21 In these studies, S-S bond cleavage is provoked by heating-usually to temperatures near 100 C or higher. In one notable exception, Zhang has shown that sulfur polymer and liquid metal composites can self-heal at room temperature, but this adhesion is based on affinity of the sulfur for the metal rather than through S-S bond exchange.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse vulcanization allowed repurposing of sulfur, a multi‐million‐ton side product of oil and natural gas refining, to form polymeric materials . These materials have been shown to be inexpensive and useful in applications such as infrared optics, catalysis, Li‐sulfur batteries, pollutant remediation, antibacterial surfaces, templates, healable materials, fertilizers, adhesives, or as insulators . With the aid of catalysts or the so‐called dynamic covalent polymerization, the monomer (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of ring‐opening polymerization (ROP) of molecular sulfur rings, researchers have created new materials directly from elemental sulfur to alleviate this problem. To date, multiple routes for producing sulfur‐polymer materials directly from waste sulfur have been proposed, including the reaction of thiols with elemental sulfur, the reaction of element sulfur with p ‐diiodobenzene, multicomponent polymerizations (MCPs) of sulfur with other molecules, sulfur radical transfer and coupling (SRTC) reaction with benzoxazine compounds, and inverse vulcanization of sulfur with vinyl groups . Among those methods, “inverse vulcanisation”, coined by Pyun et al.…”
Section: Introductionmentioning
confidence: 99%
“…To date,m ultiple routes for producing sulfur-polymer materials directly from waste sulfur have been proposed, including the reaction of thiols with elemental sulfur, [4,5] the reaction of element sulfur with p-diiodobenzene, [6,7] multicomponent polymerizations (MCPs) of sulfur with other molecules, [8,9] sulfur radical transfer and coupling (SRTC) reaction with benzoxazine compounds, [10] and inverse vulcanization of sulfur with vinyl groups. [11][12][13][14][15][16] Among those methods," inverse vulcanisation", coined by Pyun et al in 2013, [11] has gained much attention for its outstanding benefits:s imple,s olvent-free,a nd high utilization of sulfur.I ti sn otable that inverse vulcanised polymers show various advantageous functions,like mercury capture, [12,13] self-healing capability, [17,18] optical application, [19,20] electrochemical properties, [21,22] and antimicrobial properties. [23] However,p oor mechanical properties of these exciting new materials currently limit their wider application and scale of use.A lso,t here is still little literature on the mechanical properties of inverse vulcanized polymers.A ccording to the available reports, [11,17,18,[24][25][26][27][28][29][30] most materials show aq uite low strength compared to conventional polymers.T he reported highest stress of this material is 8.69 MPa of copolymer poly(S-DIB), which means that not much force is required to break the polymers.The change of crosslinkers seem to be the mostly reported method used for improving the related mechanical properties.E ither using an ew crosslinker or blending two different crosslinkers,t he rigidity modulus of sulfur-polymers could be modified from high to low,b ut the strength is...…”
Section: Introductionmentioning
confidence: 99%